Low-Density Granulocytes Are a Novel Immunopathological Feature in Both Multiple Sclerosis and Neuromyelitis Optica Spectrum Disorder - Ostendorf, Lennard; Mothes, Ronja; van Koppen, Sofie; Lindquist, Randall L.; Bellmann-Strobl, Judith; Asseyer, Susanna; Ruprecht, Klemens; Alexander, Tobias; Niesner, Raluca A.; Hauser, Anja E.; Paul, Friedemann; Radbruch, Helena (Frontiers in Immunology, 2019)
Objective: To investigate whether low-density granulocytes (LDGs) are an immunophenotypic feature of patients with multiple sclerosis (MS) or neuromyelitis optica spectrum disorder (NMOSD). Methods: Blood samples were collected from 26 patients with NMOSD and 20 patients with MS, as well as from 18 patients with Systemic Lupus Erythematosus (SLE) and 23 Healthy Donors (HD). We isolated peripheral blood mononuclear cells (PBMCs) with density gradient separation and stained the cells with antibodies against CD14, CD15, CD16, and CD45, and analysed the cells by flow cytometry or imaging flow cytometry. We defined LDGs as CD14-CD15high and calculated their share in total PBMC leukocytes (CD45+) as well as the share of CD16hi LDGs. Clinical data on disease course, medication, and antibody status were obtained. Results: LDGs were significantly more common in MS and NMOSD than in HDs, comparable to SLE samples (median values HD 0.2%, MS 0.9%, NMOSD 2.1%, SLE 4.3%). 0/23 of the HDs, but 17/20 NMOSD and 11/17 MS samples as well as 13/15 SLE samples had at least 0.7 % LDGs. NMOSD patients without continuous immunosuppressive treatment had significantly more LDGs compared to their treated counterparts. LDG nuclear morphology ranged from segmented to rounded, suggesting a heterogeneity within the group. Conclusion: LDGs are a feature of the immunophenotype in some patients with MS and NMOSD.